Brevipalpus phoenicis (Geijskes) species complex (Acari: Tenuipalpidae)—a closer look - Beard, Jennifer J.; Ochoa, Ronald; Braswell, W. Evan; Bauchan, Gary R. (Zootaxa, 2015)
Brevipalpus phoenicis sensu stricto (Geijskes) is redescribed and the species diagnosis established. Two former synonyms of B. phoenicis sensu lato, B. yothersi Baker and B. papayensis Baker, are resurrected and redescribed and their species diagnoses established. Brevipalpus hondurani Evans is also redescribed and diagnosed. Four new species, previously misidentified as B. phoenicis sensu lato or B. obovatus Donnadieu, are described—B. azores sp. nov., B. feresi sp. nov., B. ferraguti sp. nov., and B. tucuman sp. nov. Four new junior synonyms of B. yothersi are listed—Brevipalpus amicus Chaudhri and B. recula Chaudhri (new synonymies), and B. mcbridei Baker and B. deleoni Pritchard and Baker (misidentifications). A key is provided to separate these species. New morphological characters significant for species separation are presented and discussed.